The influence of prior accumulated work on the torque-cadence relationship in junior cyclists - Giorgi, A.; Martinez-Gonzalez, B.; Vicini, M.; Tarocchi, M.; Modesti, P. A.; Leo, P. (Journal of Science and Cycling, 2025)
Understanding the torque-cadence-power relationship in fatigue is crucial for assessing cyclists' performance potential. The aim of the study is to investigate the impact of prior accumulated work (like a junior cycling road race) on the power duration and torque cadence relationship. Results showed that race simulation workload induces reductions in Critical Power (CP: fresh = 301 ± 41; fatigued = 282 ± 46; p = 0.021), work capacity (W': fresh = 12497 ± 2846; fatigued = 9780 ± 2396; p = 0.009), 15 seconds, 3 minutes and 12 minutes all out efforts along with lower cadences (p < 0 .05). On the other hand, torque values did not change under fatigue across all out efforts. These findings highlight that accumulated work influences the torque-cadence-power dynamics showing that drop in power output is mainly driven by declines in cadence rather than torque.